Gra w baśnie. O relacji baśni i gier wideo - Polachowska, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article presents the new-founded relations between the genre of fairytale and its representations in video games. Following the concept of multimedia genres created by Edward Balcerzan, the article demonstrates a holistic view of the term “genre”. It combines it with the media theory by Krzysztof Kozłowski, which emphasizes social connotations of each medium and their ability to represent different genres. On the other hand, each and every genre can manifest itself through various media that enables mutual development. This theory finds its reflection in the analysis of the above-mentioned relations. The author applies the theoretical tools used for the analysis and interpretation of literary fairytales to video games based on the fairytale motifs. Two chosen examples, Trine by the Frozenbyte studio and Brothers: A Tale of Two Sons by the Starbreeze studio, represent not only a new way to fulfill the potential of the genre, but also innovative solutions in the evolution of gaming.